An interactive C++ programming courseware (SIFOO) / Mazliana Hasnan … [et al.] - Hasnan, Mazliana; Othman, Zainab; Mohamad, Norizan; Abdullah, Zamlina (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Learning programming is fundamental to a Computer Science student. However, many students find it difficult to master the programming subject. An interactive C++ courseware (SIFOO) has been developed to assist the students gaining and testing their programming skills as well as understanding in C++ programming language. SIFOO consists of interactive fundamentals of Computer Problem Solving with a combination of brief lecture notes, program examples, exercises and tests. Students can refer to a particular topic or a specific training repeatedly without time limits depending on the needs and abilities of students. This application was designed based on the learning theory perspective and basic principles user interface design. The development process adopted the ADDIE model that involved four phases which are Analysis, Design, Development, Implementation and Evaluation. SIFOO can be implemented for all UiTM branches in Malaysia and also UiTM franchised colleges.